High ecological and human health risks from microcystins in vegetable fields in southern China. (December 2019) - Xiang, Lei; Li, Yan-Wen; Liu, Bai-Lin; Zhao, Hai-Ming; Li, Hui; Cai, Quan-Ying; Mo, Ce-Hui; Wong, Ming-Hung; Li, Qing X.
Abstract: Frequent cyanobacterial blooms in the eutrophic waters produce a variety of toxins such as the monocyclic heptapeptide microcystins, greatly harming aquatic ecosystems and human health. However, little information of microcystins in agricultural fields is known. This field study of three common microcystin variants (MC-LR, MC-RR, and MC-YR) in vegetables ( n  = 161), soils ( n  = 161) and irrigation water samples ( n  = 23) collected from southern China regions affected by cyanobacteria blooms, shows their prevalence with total concentrations up to 514 μg/L water, 187 μg/kg soil (dry weight) and 382 μg/kg vegetable (fresh weight). MC-RR was the primary variant in all types of samples, accounting for 51.3–100% of total microcystin concentrations. Significant concentration-dependent correlations ( p  < 0.05) demonstrated that microcystin-contained irrigation waters were the major source of microcystin accumulation in both vegetables and soils. Meanwhile, intracellular-microcystins in irrigation water was found to play an important role in microcystins bioaccumulation in vegetables for the first time. Most vegetable samples (≥60%), particularly celery posed moderate or high human health risk via diet based on toxicity equivalents of the microcystins and reference dose for MC-LR (0.04 μg/kg/d), showing high food safety hidden dangers. Soil microcystins, especially MC-RR in 46.4–88.3% of soils could pose high ecological risks. This study highlights the potential high ecological and human health risks of microcystins in the real soil-vegetable systems of areas affected by cyanobacteria blooms, implying the profound significance and urgent need of investigation on microcystins in terrestrial ecosystems. Graphical abstract: Unlabelled Image Highlights: MCs are prevalent in actual soil-crop systems affected by cyanobacterial blooms. MC-RR was the primary variant in all types of the samples. Intracellular-MCs could play an important role in vegetable MCs accumulation. Most vegetable samples posed moderate or high human health risk via diet. Soil MCs, especially MC-RR could pose high ecological risks.